Duodenal adenocarcinoma: Advances in diagnosis and surgical management - Cloyd, Jordan M (World J Gastrointest Surg, 2016)
Duodenal adenocarcinoma is a rare but aggressive malignancy. Given its rarity, previous studies have traditionally combined duodenal adenocarcinoma (DA) with either other periampullary cancers or small bowel adenocarcinomas, limiting the available data to guide treatment decisions. Nevertheless, management primarily involves complete surgical resection when technically feasible. Surgery may require pancreaticoduodenectomy or segmental duodenal resection; either are acceptable options as long as negative margins are achievable and an adequate lymphadenectomy can be performed. Adjuvant chemotherapy and radiation are important components of multi-modality treatment for patients at high risk of recurrence. Further research would benefit from multi-institutional trials that do not combine DA with other periampullary or small bowel malignancies. The purpose of this article is to perform a comprehensive review of DA with special focus on the surgical management and principles.